Optimization of Soya Phosphatidylcholine and Tween 80 As A Preparation of Diclofenac Sodium Transfersome Vesicles Using Design-Expert: Optimasi Fosfatidilkolin Kedelai dan Tween 80 Sebagai Penyusun Vesikel Transfersom Natrium Diklofenak Menggunakan Design- Expert - Wa Ode Sitti Zubaydah; Rina Andriani; Suryani Suryani; Astrid Indalifiani; Sitti Raodah Nurul Jannah; Devi Hidayati (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2023)
Background: Diclofenac sodium is a non-steroidal anti-inflammatory drug (NSAID) widely prescribed for inflammation and pain. However, when used orally, diclofenac sodium has poor bioavailability because it undergoes first-pass metabolism in the liver, so only about 50% of the drug reaches systemic circulation. Therefore, the transdermal delivery system, in this case, transfersome nanovesicles, was chosen as an alternative to overcome these problems. Transfersome is a lipid vesicle with the best deformability in penetrating the skin layer among other nanovesicles. Transfersomes consist of active substances, phospholipids, surfactants, and other ingredients. The composition of phosphatidylcholine as a phospholipid and tween 80 as a surfactant is a variable that can affect the optimization of the transfersome formula. Therefore, the ratio of phospholipids and surfactants should be varied to obtain the most stable transfersome formula with high drug entrapment efficiency. Optimization as an approach to get the best combination of a formula can be done in a more efficient way using software called Design-Expert. This software is used to help carry out experimental designs, such as determining the optimum formula for a preparation. Objectives: This study aims to determine the ratio of soya phosphatidylcholine as a phospholipid and tween 80 as a surfactant in the optimum formula of diclofenac sodium transfersome vesicles using Design-Expert and to determine the characteristics of the resulting transfersome vesicles. Material and Methods: Optimizing the transfersome Diclofenac Sodium formula using the factorial design 22 with soya phosphatidylcholine and tween 80 factors, particle size response, and entrapment efficiency. The thin layer hydration method carried out the process of making diclofenac sodium transfersome. Results: The results obtained from this study, namely the optimum formula based on Design-Expert, obtained a ratio of soya phosphatidylcholine and tween 80 of 4.5%: 0.5%. The results of the characterization of the optimum formula obtained a particle size of 224.3 nm, a zeta potential of -57.1 mV, and entrapment efficiency of 99.85%. Conclusions: The results of the characterization of the diclofenac sodium transfersome have met the specifications required for each test.